Lie group analysis for MHD squeezing flow of viscous fluid saturated in porous media - G. Magalakwe; M.L. Lekoko; K. Modise; Chaudry Masood Khalique (Alexandria Engineering Journal, 2019)
A two-dimensional laminar flow driven by fluid injection through porous surface which represent an incompressible fluid inside a filtration chamber during extraction of particles from the fluid is investigated. The study constructs a mathematical model that represents internal flow field during filtration process proficiently by using basic conservation laws of mass, momentum and energy. For better understanding of dynamics of the case study, solutions that lead to stable filtration process (balanced dynamical system) are obtained and consequently provide an insight of the important dynamics that lead to an optimal filtration process. The solution of partial differential equations representing the internal flow field similarity transformation based on Lie group method is utilized to reduce the system to ordinary differential equations. Thereafter, double perturbation method is employed to determine semi-analytical solutions of reduced system. Effects of various parameters that arise from the configuration (design) of the filter are presented graphically and analysed to show the connection between the case study and findings. Keywords: Two-dimensional viscous laminar flow, Stable filtration process, Lie group analysis, Perturbation method